Strategic Partnership between Russia and China: Importance and Sustainability of Bilateral Relations - A. V. Sharyshev (Сравнительная политика, 2016)
In the light of the present political situation in the world, namely complex relations between Russia and the West, on the one hand, and existing tensions between China and some of its regional neighbors, on the other, strategic partnership between Russia and China is gaining more and more importance for the both countries. The article aims to outline the reasons for maintaining and developing further bilateral partnership and explains the sustainability of those relations in contemporary context.